DEVELOPING LOCAL INSTRUCTION THEORY FOR LEARNING PERMUTATION USING REALISTIC MATHEMATICS EDUCATION - Ika Meika; Asep Sujana (Euclid, 2024)
Permutation is fundamental topic in combinatorics that support students’ understanding of probability, statistics, and mathematical reasoning. However, many students experience difficulties in distinguishing permutation from combination and in applying counting principles in contextual situations. This study aims to develop a local instruction theory (LIT) for learning permutation based on the Realistic Mathematics Education (RME) approach. The research employed design research consisting of three phases: preliminary design, teaching experiment, and retrospective analysis. The participants were senior high school students in Indonesia. Data were collected through observations, student worksheet, interviews, and classroom documentation. The results indicate that the developed learning trajectory supports students in constructing permutation concepts gradually from informal strategies toward formal mathematical representation. The learning trajectory includes contextual exploration, modelling using diagrams and tables, pattern recognition, generalization, and application of permutation formulas. The findings suggest that the developed LIT can facilitate students’ conceptual understanding and mathematical modelling abilities. This study contributes to mathematics education research by providing a theoretically grounded instructional design for teaching permutation.